Kajian Etnobotani Pemanfaatan Tumbuhan dalam Praktik Ritual Mecaru di Candi Singosari Kabupaten Malang - Auliya Maulida Kasana; Senja Dewi Farahita; Zidni Nafi’atul Ilma; Fahrul Ghani Muhaimin; Nafi’ Windy Kharisma; Syifa Nabila Firdausya; Heni Refdiana; Anas Bagaskara Witanto; Ayu Chandra Mustikasari; Susriyati Mahanal (Biocaster : Jurnal Kajian Biologi, 2026)
The use of plants in the Mecaru ritual at Singosari Temple represents an important aspect of local wisdom that is at risk of decline due to limited scientific documentation and the influence of modernization. This study aims to document and examine local community knowledge regarding the use of plants in the Mecaru ritual at Singosari Temple, Malang Regency. The research employed a descriptive qualitative approach, with data collected through observation, semi-structured interviews, and documentation. Informants were selected purposively and expanded using the snowball sampling technique. The results revealed that 11 plant species belonging to 9 families were utilized, with various growth forms including trees, herbs, shrubs, and bushes. The most commonly used plant parts were flowers, followed by leaves and fruits, with most of them used in fresh condition. These plants hold philosophical meanings related to spiritual values, symbols of purity, and expressions of gratitude in community life. In general, the conservation status of these plants has not been widely identified; however, the practice of utilizing local plants reflects efforts toward the sustainable use of resources. These findings highlight the important role of the Mecaru ritual in preserving local wisdom, strengthening ethnobotanical studies, and supporting cultural and environmental sustainability.